PENGARUH KEPEMIMPINAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN BANK DKI JAKARTA - Muhammad Reza Anwar Nurdin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
The leadership problem has become a separate problem for the management of Bank DKI Jakarta, where the past few years have shown that there is a decrease in the performance of each manager, where this decline occurs due to a decrease in the performance of each individual employee below. The application of bad leadership will have an impact on the achievement of corporate goals obtained from not the maximum results achieved from each individual employee. On the other hand, in anticipating vacancies in certain positions and in improving job skills and skills, the company provides training for employees in the hope that all of the goals and objectives of the company can be achieved. The purpose of this study was to analyze the influence of leadership and training both simultaneously on employee performance at Bank DKI Jakarta. In primary data collection the author involved 57 permanent employees at the Bank DKI Jakarta head office. The technique of analysis uses simple regression analysis and multiple regression. The results showed that there were influences both partially and simultaneously leadership variables and training on employee performance.